THE STUDY OF MAGNETITE ORE PREPARATION AS DENSE MEDIUM SEPARATOR MEDIA FOR COAL WASHING USING MAGNETIC SEPARATION â GRINDING PROCESS - Fadhilah, Rifdah
In Indonesia, one of the coal companies that used magnetite as a media for dense medium separator in coal washing is Kaltim Prima Coal. Magnetite which is used in Kaltim Prima Coal is originated from Australia because the iron ore in Indonesia has not been utilized well until now. Therefore a research about the right preparation of the magnetite ore in Indonesia is needed so it could meet the required specification to be used as a media for coal washing. The ore used for this research is Lampung magnetite ore which had been prepared by LIPI Lampung. The methods used to get the same characteristics as magnetite ore from Australia that fulfill the specification standard were by concentrated magnetic minerals using magnetic separator then grinding followed by sieving analysis. Magnetic separator was used for concentrating ?95% magnetic content. The variables used for this process are magnetic rotor speed and current. Afterwards the optimum current for concentrating the best Fe recovery was determined. Grinding was used for comminuting the concentrated minerals until obtained P95 53 ?m. Sample characterizations have been done by the sample from the whole processes of the explained methods. Characterization have been done by polish section, XRD, XRF, AAS, and VSM. Furthermore relative density measurement have been done. The result of XRD and mineragraphy analysis shows that magnetite is the dominant mineral from all the three samples. VSM analysis results magnetic saturation, magnetic remanence, and coercivity values of Australia magnetite greater than concentrated samples, however magnetic remanence and coercivity of the concentrated samples increased when compared with raw Lampung magnetite ore. The increasing current of magnetic separator reduces Fe grade and increases Fe concentrate recovery. Whereas increasing the magnetic rotor rotation speed increases Fe grade and reduces Fe concentrate recovery. The best Fe recovery shows by 0.8 A current with 15 rpm magnetic rotor rotation speed is 97.95%. The increasing grinding duration and mill rotation speed produce more fine particles. P95 53 ?m acieved at 120 minutes grinding time with 60 rpm mill rotation speed. Magnetic content and cummulative passing percentage of 53 ?m sieve of concentrated Lampung magnetite by experiment show the value of 95.18% and 97.11% which is achieved the specification. Whereas relative density of concentrated Lampung magnetite by experiment shows the value of 4.53 gr/cm3 which is not reached the specification.